PENGEMBANGAN PARIWISATA BERBASIS AGROWISATA MELALUI PENGUATAN PERAN KELOMPOK WANITA TANI (Studi Di Desa Sungai Langka Kecamatan Gedong Tataan Kabupaten Pesawaran): Studi Di Desa Sungai Langka Kecamatan Gedong Tataan Kabupaten Pesawaran (Administratio, 2019)
Agricultural-tourism development is one of alternatives that can encourage economic potential. Utilization potential of natural resources often not performed optimally. Development of agriculture-tourism in the Sungai Langka Village will done by prioritizing the empowerment of women by forming a group of women farmers as one of the strategic activities in realizing the participatory development as well as join in creating the condition of women that defenseless. This research aims to analyze the agro tourism-based development of tourism through strengthening the role of the farmer women’s group in the village of Sungai Langka. The type of research is qualitative based on gender perspective. Data collection had done by interviews, documentations, and observations. Based on the research that had been done can be concluded that the development of agroculture-tourism in Sungai Langka including Community Based Tourism and the implementation has already been optimal. In the development of agro-tourism, there are some factors like age, gender, education, occupation, and length of stay, but not education can’t besupporting factor. As consideration, Department of Agriculture and Department of Tourism in Pesawaran Regency provide training to process agricultural products to farmer women’s group and communities, subdistrictand full fil facilities and infrastructure as well as the promotion aspect and women farmers in Sungai Langka Village dare to use funds from the Government in developing the agricultural-tourism. Keywords: development, agrocultural-tourism, groups of women farmers, community based tourism